EDUCAŢIA ŞI PROVOCĂRILE LUMII CONTEMPORANE - USM ADMIN (Moldova State University, 2011)
One of the most important elements of contemporary society is its change; we live in a rapidly changing spectacular. The third millennium has inherited many social problems: economic and political ones. More serious global problems are to be dealt with. Education and the standard of living is different in various countries, there is a feeling of disappointment among many people.